ANALISIS PENDAPATAN PETANI KEMIRI DI DESA AIMOLI KECAMATAN ALOR BARAT LAUT KABUPATEN ALOR - Demang, Ferdinan; Maure, Gerson Hans (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2024)
Candlenut is one of the plants that has great potential to be developed in community life. The research was conducted in Aimoli Village, Alor Barat Laut District from April to August 2024. The sample size was 70 people using the Slovin formula. Data collection through direct interviews with respondents, publication data from the Central Statistics Agency of Alor Regency and the Agriculture and Plantation Service of Alor Regency. The study aims to analyze farmers' income and the feasibility of candlenut farming in Aimoli Village, Alor Barat Laut District. The results of the study showed that the income of candlenut farmers in Aimoli Village was 16,379,754 and the R/C Ratio was greater than 1 so that candlenut farming was profitable and feasible to be pursued.